Use of waste in road paving (Research, Society and Development, 2021)
This research will work on the use of solid waste in road paving, considering that new methodologies have been drawn up to offer greater efficiency to this process, and all the economic and ecological benefits derived from the reuse of these materials in such processes. In a qualitative way based on bibliography, it aims to answer the following problem: How does the reuse of waste occur on the road pavement? This work aims to study the state of the process that uses waste in road paving, focusing on the methods used in each type of waste, performance and its main characteristics. The study of the use of waste in road paving is justified in view of the growing need to make better use of available resources. Therefore, when researching this topic, in addition to advancing the environmental factor, the economic issue can be developed, which is often one of the motivational aspects much more appreciated by entrepreneurs in the construction industry.